Pengembangan Strategi Kompetetif Pt Bangun Kosambi Sukses Tbk, Melalui Pendekatan Blue Ocean Strategy - Surya Soebroto (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
This study aims to analyze the business strategy of PT Bangun Kosambi Sukses Tbk (CBDK) in addressing competition in the property industry using the Blue Ocean Strategy approach. The analysis employs PEST Analysis, Porter's Five Forces, Value Chain Analysis, Competitive Profile Matrix (CPM), and the Four Actions Framework. The results indicate that CBDK's key strengths lie in its strategic location and business growth, while its main challenges include limited brand awareness and market share. The proposed strategy focuses on developing a property-as-a-service concept, integrating digital technology, strengthening the live-work-stay ecosystem, and implementing ESG principles to create new value and enhance the company's competitive advantage.